The structure of the scientific perception of the world, sanctification for knowledge or secularization of it? - Kara, Sabah (Arab Journal for Sciences and Research Publishing, 2022)
The perceptions of the world have an effective functional role as an explanatory means of the laws and systems of the universe and an answer to the human being about his various crucial questions, including existential, epistemological and value.These perception branch into types, the most famous of which are philosophical, religious and scientific.This article will be concerned with the perception scientific, which enjoys wide acceptance and spread, by extending its concept and searching for its most important features and principles, in addition to monitoring the most important crises resulting from it, in order to ask in the end about the relationship of the scientific perception wich holiness, meaning is the knowledge resulting from the scientific perception a sacred ladle respected the transcendement thruth, or is it a declared imperialiste materialism that violate man and nature and reprisents an instrument of domination, as Francis Bacon said: «the knowledge is power»
Keywords: world perception; Scientific perception; sacred knowledge; secularized knowledge